Sintesa dan Karakterisasi Bioplastik Dari Tandan Kosong Kelapa Sawit Dengan Modifikasi Penambahan Plasticizer Gliserol dan Sorbitol - Luthfi, Muhammad Zulfikar; Miftahurrahmah, Miftahurrahmah; Sutri, Reni; Nury, Dennis Farina (REACTOR: Journal of Research on Chemistry and Engineering, 2025)
Plastic waste is a global environmental issue due to its non-biodegradable nature. One potential solution is the development of eco-friendly bioplastics derived from natural materials. This study aims to develop bioplastics based on sago starch with the addition of microfibrillated cellulose (MFC) from empty palm oil fruit bunches as a reinforcing filler to enhance mechanical properties. Additionally, plasticizers such as glycerol and sorbitol were added to improve the elasticity of the bioplastic. The plasticizer concentrations used were 1, 5, 10, 20, and 30% w/w. Characterization was conducted through mechanical property tests (tensile strength, elastic modulus, and elongation percentage), morphological analysis using SEM, and structural analysis with Fourier Transform Infrared Spectroscopy (FTIR spectroscopy). The results showed that the addition of 5% glycerol produced a tensile strength of 26.39 MPa with an elongation of 1.2%, while 20% sorbitol yielded a tensile strength of 25.35 MPa with an elongation of 6.2%. Based on the Indonesian National Standard (SNI) for plastics, the combination of sago starch and MFC with 20% sorbitol provided the best mechanical properties, with a tensile strength of 25.35 MPa and an elongation percentage of 5.6%. In conclusion, sago starch-based bioplastic with MFC from oil palm empty fruit bunches has the potential to serve as an environmentally friendly alternative to synthetic plastics.